The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/en14092527
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Prospective Average and Marginal GHG Emission Factors—Scenario-Based Method for the German Power System until 2050

Abstract: Due to the continuous diurnal, seasonal, and annual changes in the German power supply, prospective dynamic emission factors are needed to determine greenhouse gas (GHG) emissions from hybrid and flexible electrification measures. For the calculation of average emission factors (AEF) and marginal emission factors (MEF), detailed electricity market data are required to represent electricity trading, energy storage, and the partial load behavior of the power plant park on a unit-by-unit, hourly basis. Using two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Emission factors from electricity production are known to vary significantly depending on the energy mix and other conditions considered in their evaluation [83,84]. As discussed in our recent study [85], the emission factor of CO 2 can vary between close to zero values for an almost exclusively renewable energy-based mix up to 700 to 900 kg/MWh for coaland oil-fired power plants.…”
Section: Discussionmentioning
confidence: 86%
“…Emission factors from electricity production are known to vary significantly depending on the energy mix and other conditions considered in their evaluation [83,84]. As discussed in our recent study [85], the emission factor of CO 2 can vary between close to zero values for an almost exclusively renewable energy-based mix up to 700 to 900 kg/MWh for coaland oil-fired power plants.…”
Section: Discussionmentioning
confidence: 86%
“…Several researchers use a single average country-related value while others incorporate power import and export and yet others recommend using marginal factors [103] that might vary seasonally as well as during a single day depending on the actual balance of the grid [104]. Moreover, with increasing use of renewables in the electric energy production sector [105], the corresponding emission factor values are likely to decrease in future, which should also be considered [106,107]. Therefore, it makes little sense to use a single emission factor value and two distinctive scenarios were set up: one adopting the emission factor of Slovenské elektrárne, a.s., adopted from our previous study [108]; and the other one the emission factor of a conventional coal power plant [109].…”
Section: Energetic and Environmental Evaluationmentioning
confidence: 99%
“…Carbon dioxide emissions are considered as the most relevant ones in this regard and a lively debate on the correct attitude towards calculation and evaluation of its emission factors is in progress [49,50]. It is generally agreed that marginal emission factors (MEF) should better represent the real impact of power consumption change on the related CO2 emissions [51,52]. For even more precise carbon accounting for processes with very variable power demand, daily or even hourly MEF are recommended to be applied [53].…”
Section: Greenhouse Gas Emissions Attributable To Asu Operationmentioning
confidence: 99%
“…Even though power production becomes gradually cleaner as advanced techniques and flue gas cleaning systems are adopted in thermal plants and old plants are ruled out of service [58], MEF values were agreed to be highly spatiotemporally specific. Thus, recent studies employing the MEF always relate them to a specific period and country [52,59], thus requiring reliable structural data about power sources and transmission system operation [60]. A recent extensive review by Hamels et al [49] evaluating over 100 related studies revealed both the absence of a unified approach to the estimation of GHG emissions related to power production and consumption and the significant variability of individual emission factors.…”
Section: Greenhouse Gas Emissions Attributable To Asu Operationmentioning
confidence: 99%
See 1 more Smart Citation